CFD ANALYSIS OF MODIFIED IMPELLER FOR PAINT MIXER - Azmin, Muhammad Danial (IRC, 2020)
By using the Computational Fluid Dynamics (CFD) program, the impeller's output could be visualized without creating a prototype which would cost the time and money. For this research, simulation of computational fluid dynamics is performed on two forms of impeller design (Counterflow and Sawtooth) and modification of their design (4-Sided Impeller and Inclined Blade Sawtooth Impeller) for evaluation 2 technique of simulating was used to analyse the rotation of the impellers which are the Multiple Reference Frame method and the Moving Wall method. The simulations result shown by vector of velocity and wall shear of vectors. The efficiency of the impellers is then measured on the basis of the result obtained comparatively. The results of this project are important in determining an effective impeller to mix industrial paint in a homogeneous way.